Pourable in-situ solidified phase change heat storage flame-retardant thermal insulation composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611356332.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-30
AI Technical Summary
其重点在于轻质阻燃隔热灌封,未将相变储热单元、反应隔离型膨胀阻燃单元及绝缘导热调控单元结合起来,因而难以同时覆盖电池正常运行、异常升温和热失控蔓延等不同热安全阶段
本发明以双组分加成固化有机硅体系作为连续相,通过控制各功能单元的组成及界面状态,使未固化复合材料能够进入电池单体之间以及电池单体与壳体之间的间隙,并在灌注位置原位固化形成连续的弹性复合体,从而兼顾灌注施工、功能填料固定和模组部件弹性支撑。
Smart Images

Figure CN123018259A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of phase change thermal storage flame retardant insulation materials, and in particular to an injectable in-situ curable phase change thermal storage flame retardant insulation composite material, its preparation method, and its application. Background Technology
[0002] New energy vehicle power batteries continuously generate heat during charging and discharging. When heat dissipation is uneven within the battery module or localized heat cannot be dissipated in time, temperature gradients and localized hot spots can easily form. This not only affects the battery's charging and discharging performance, cycle life, and consistency, but may also induce separator shrinkage, electrolyte decomposition, and heat propagation between adjacent battery cells. Active thermal management structures such as liquid cooling plates and air-cooled channels can remove heat under normal operating conditions, but their ability to suppress transient thermal shocks and heat propagation between adjacent battery cells is limited when the cooling system fails, there are abnormal local connections, or battery cells rapidly release heat.
[0003] Phase change materials (PCMs) can absorb and temporarily store heat during phase change processes, thus reducing the temperature rise rate and temperature non-uniformity of battery modules. However, commonly used organic PCMs often suffer from problems such as liquid phase flow, easy leakage, and flammability. Microencapsulating PCMs can limit leakage to some extent, but shell damage can still occur during high-shear mixing, vacuum degassing, filling, and long-term thermal cycling. Furthermore, using PCMs alone is mainly suitable for heat buffering near normal operating temperatures; their flame retardancy, heat insulation, and high-temperature barrier capabilities remain limited once the battery cell enters high-temperature or thermal runaway stages.
[0004] Chinese patent application CN107815286A discloses a thermally conductive potting silicone based on phase change microcapsules and its preparation method. By introducing phase change microcapsules and thermally conductive fillers into a two-component addition-curing silicone system, the potting material achieves both heat storage and thermal conductivity. Its focus is on phase change heat storage and thermally conductive potting. However, issues remain unresolved regarding the shell stability of the phase change microcapsules during complex potting processes, the influence of flame-retardant components on the addition curing reaction, and the high-temperature thermal insulation barrier under thermal runaway conditions.
[0005] Chinese patent application CN113789157A discloses the application of spray-applied phase change materials in batteries. The materials include phase change microcapsules, vinyl silicone oil, hydrogen-containing silicone oil, and related additives, suitable for application to the battery surface via spraying. However, due to its primary surface coating method, further improvements are needed in areas such as continuous filling within narrow gaps in battery modules, structural fixation of the phase change unit, elastic support of module components, and control of heat transfer paths in different areas.
[0006] Chinese patent application CN115595091A discloses an ultra-low density, ultra-flame-retardant silicone thermal insulation potting compound and its preparation method. It achieves low density, flame retardancy, and thermal insulation properties through the combination of lightweight flame-retardant fillers and a silicone system. However, its key feature is the lightweight flame-retardant thermal insulation potting compound. It does not integrate the phase change thermal storage unit, the reaction-isolated expansion flame-retardant unit, and the insulation and thermal conductivity regulation unit, thus making it difficult to simultaneously cover different thermal safety stages, such as normal battery operation, abnormal temperature rise, and thermal runaway propagation.
[0007] Directly mixing phase change materials, intumescent flame retardants, thermally conductive fillers, and thermally insulating fillers in organosilicon potting systems can easily lead to problems such as phase change material leakage, flame retardant components interfering with platinum catalytic addition curing, conductive carbon materials reducing volume resistivity, filler agglomeration causing increased slurry viscosity, and mutual constraints between thermal conductivity and thermal insulation.
[0008] Therefore, it is necessary to provide a composite material that can be infused and cured in situ inside a battery module, so that it has the functions of heat storage and uniform temperature and moderate thermal conductivity during normal operation, heat absorption and buffering during abnormal temperature rise, and flame-retardant and heat-insulating barrier during thermal runaway, while meeting the requirements of electrical insulation, infusion construction and structural fixation. Summary of the Invention
[0009] In view of this, the present invention provides a potable, in-situ curable phase change thermal storage flame-retardant and heat-insulating composite material, its preparation method, and its application. The present invention synergistically disperses a double-shell microcapsule phase change thermal storage unit, an endothermic inorganic flame-retardant unit, a reaction-isolated expansion flame-retardant microcapsule, a high-temperature heat-insulating barrier unit, and an insulating and thermally conductive regulating unit within a two-component addition-curing organosilicon reaction system. Employing a potable, in-situ curing, and zoned heat transfer regulation structure, it achieves uniform temperature during normal operation, heat buffering during abnormal temperature rises, and flame-retardant and heat-insulating barrier formation during thermal runaway. Simultaneously, it considers slurry potability, curing stability, electrical insulation, and module structure fixation performance, showing promising application prospects in the thermal safety protection and integrated potting of new energy vehicle power battery modules.
[0010] The first aspect of this invention provides an injectable, in-situ curable phase change heat storage, flame retardant, and heat insulation composite material, comprising component A and component B, which are stored separately and undergo a cross-linking and curing reaction after mixing. Based on the total mass of components A and B, the composite material includes: 20%~38% addition-cured silicone reactive matrix; 25%~40% double-shell microcapsule phase change heat storage unit; 8%~20% endothermic inorganic flame retardant unit; 4%~12% reaction-isolated expansion flame retardant microcapsules; 1%~8% high-temperature thermal insulation barrier unit; 2%~15% thermal insulation and thermal conductivity regulation unit; 0.2%~3% curing and process auxiliary unit, the sum of the mass percentages of all components is 100%; The addition-cured silicone reactive matrix forms an elastic reactive matrix and provides electrical insulation; the double-shell microcapsule phase change thermal storage unit absorbs heat in the phase change temperature range and restricts the flow of the core material; the endothermic inorganic flame retardant unit decomposes upon heating, absorbs heat, and releases moisture; the reaction-isolated intumescent flame retardant microcapsule isolates the reactive flame retardant core material and forms an intumescent char layer upon heating; the high-temperature thermal insulation barrier unit forms a porous flame retardant and thermal insulation structure at high temperatures; the insulation and thermal conductivity regulation unit adjusts the thermal conductivity of the cured body and maintains electrical insulation; and the curing and process auxiliary unit regulates the curing speed, dispersibility, defoaming, and rheological properties. The addition-cured organosilicon reaction matrix includes vinyl-terminated polyorganosiloxanes and hydrogen-containing polyorganosiloxanes; The curing and process aid unit includes at least one of platinum-based catalysts, curing inhibitors, dispersants, defoamers, silane coupling agents, fumed silica, and tracer pigments; The double-shell microcapsule phase change thermal storage unit includes a phase change material core, a polyurea inner shell layer formed by the interfacial polymerization of isophorone diisocyanate and diethylenetriamine, and a silica outer shell layer formed by the sol-gel reaction of tetraethyl orthosilicate and covering the outside of the polyurea inner shell layer. The heat-absorbing inorganic flame-retardant unit includes aluminum hydroxide and boehmite; The reaction-isolated intumescent flame-retardant microcapsule comprises an intumescent flame-retardant core material composed of ammonium polyphosphate, pentaerythritol and melamine, and a polyurea primary shell layer and a silica outer shell layer sequentially covering the intumescent flame-retardant core material. The high-temperature thermal insulation barrier unit includes hydrophobic silica aerogel composite microparticles, surface silanized hollow glass microspheres, and silica-coated expandable graphite. The insulating and thermally conductive control unit comprises spherical alumina and hexagonal boron nitride; After the components A and B are mixed and cured, a cross-linked silicone elastomer is formed. The double-shell microcapsule phase change heat storage unit, the heat-absorbing inorganic flame retardant unit, the reaction-isolated expansion flame retardant microcapsule, the high-temperature heat insulation barrier unit, and the insulation and thermal conductivity regulation unit are dispersed and fixed in the cross-linked silicone elastomer.
[0011] Preferably, the vinyl-terminated polysiloxane comprises a first vinyl-terminated polysiloxane with a viscosity of 50-300 mPa·s at 25°C and a second vinyl-terminated polysiloxane with a viscosity of 800-1500 mPa·s at 25°C, wherein the molar ratio of the silane-hydrogen bonds in the hydrogen-containing polysiloxane to the vinyl groups in the vinyl-terminated polysiloxane is 0.8-1.5.
[0012] Preferably, component A comprises vinyl-terminated polysiloxane and platinum-based catalyst and does not contain hydrogen-containing polysiloxane, and component B comprises vinyl-terminated polysiloxane, hydrogen-containing polysiloxane and curing inhibitor and does not contain platinum-based catalyst; the intumescent flame-retardant core material is isolated from the platinum-based catalyst, hydrogen-containing polysiloxane and vinyl-terminated polysiloxane through the polyurea primary shell and the silica outer shell.
[0013] Preferably, the phase change material core material includes at least one of a first phase change material and a second phase change material; the first phase change material is composed of n-octadecane and n-eicosane in a mass ratio of 65:35, and the second phase change material is composed of n-eicosane and n-docosahexadecane in a mass ratio of 30:70; the phase change material core material accounts for 72% to 88% of the mass of the double-shell microcapsule phase change thermal storage unit, and the D of the double-shell microcapsule phase change thermal storage unit... 50 The size is 5~15 μm.
[0014] Preferably, the polyurea inner shell layer accounts for 6% to 15% of the mass of the double-shell microcapsule phase change thermal storage unit, and the silica outer shell layer accounts for 3% to 10% of the mass of the double-shell microcapsule phase change thermal storage unit.
[0015] Preferably, the double-shell microcapsule phase change thermal storage unit includes a first phase change microcapsule using the first phase change core material and a second phase change microcapsule using the second phase change core material; the phase change temperature of the first phase change microcapsule is 33℃~37℃, the phase change temperature of the second phase change microcapsule is 41℃~45℃, and the mass ratio of the first phase change microcapsule to the second phase change microcapsule is 1:4~4:1.
[0016] Preferably, the mass ratio of aluminum hydroxide to boehmite is 1.5:1 to 4:1.
[0017] Preferably, the mass ratio of ammonium polyphosphate, pentaerythritol, and melamine is 6:2:2; the polyurea primary shell accounts for 2% to 8% of the mass of the reaction-isolated intumescent flame-retardant microcapsule, and the total mass of the polyurea primary shell and the silica outer shell accounts for 6% to 14% of the mass of the reaction-isolated intumescent flame-retardant microcapsule.
[0018] Preferably, the silica coating amount of the silica-coated expandable graphite is 8% to 10% of the mass of the expandable graphite, the silica shell thickness is 80 to 150 nm, and the initial expansion temperature is 180°C to 200°C.
[0019] Preferably, the D of the hydrophobic silica aerogel composite microparticles 50 The D-value of the surface-silanized hollow glass microspheres is 20~80 μm. 50 The size is 20~60 μm.
[0020] Preferably, the mass ratio of the spherical alumina to hexagonal boron nitride is 3:1 to 5:1.
[0021] A second aspect of the present invention provides a method for preparing the composite material, comprising the following steps: S1. The phase change material core material is emulsified and dispersed in an aqueous phase. An interfacial polymerization reaction of isophorone diisocyanate and diethylenetriamine is used to form a polyurea inner shell layer on the surface of the phase change material core material. A silica outer shell layer is formed on the surface of the polyurea inner shell layer by a sol-gel reaction of tetraethyl orthosilicate, thus obtaining a double-shell microcapsule phase change thermal storage unit. S2. Ammonium polyphosphate, pentaerythritol and melamine are combined in a mass ratio of 6:2:2 to form an intumescent flame-retardant core material. A polyurea primary shell and a silica outer shell are sequentially formed on the surface of the intumescent flame-retardant core material to obtain reaction-isolated intumescent flame-retardant microcapsules. S3. An alkaline catalytic sol-gel reaction of tetraethyl orthosilicate is used to form a silica shell on the surface of expandable graphite to obtain silica-coated expandable graphite. S4. Mix vinyl-terminated polyorganosiloxane, platinum catalyst and at least one selected from double-shell microcapsule phase change heat storage unit, heat-absorbing inorganic flame retardant unit, reaction isolation type expansion flame retardant microcapsule, high temperature heat insulation barrier unit and insulation and thermal conductivity regulation unit to prepare component A. S5. Mix the vinyl-terminated polysiloxane, the hydrogen-containing polysiloxane, the curing inhibitor, and the remaining components (excluding component A) to obtain component B. S6. Mix the components A and B by metering and degas under vacuum to obtain an injectable reactive slurry.
[0022] Preferably, when preparing components A and B, after adding the double-shell microcapsule phase change thermal storage unit, the stirring linear speed is controlled to be no more than 5 m / s, and after adding hydrophobic silica aerogel composite microparticles and surface silanized hollow glass microspheres, the stirring linear speed is controlled to be no more than 2 m / s; after mixing components A and B, degassing is performed for 2~20 min under an absolute pressure ≤20 kPa.
[0023] A third aspect of the present invention provides a potting method for a power battery module for new energy vehicles, comprising: The components A and B of the composite material are metered and mixed and then degassed. The mixed injectable reactive slurry is injected from the bottom or lower side of the power battery module, so that the injectable reactive slurry fills at least part of the gaps between adjacent power battery cells, between power battery cells and module housing, and between power battery cells and cooling components under the action of at least one of gravity, pressure difference and vacuum assistance. The injectable reactive slurry is cured in situ at a temperature of 10℃ to 80℃. Among them, during the injection and curing process, an unsealed venting channel is retained that is connected to the safety pressure relief component of the power battery cell.
[0024] A fourth aspect of the present invention provides a power battery module for a new energy vehicle, comprising a module housing, a plurality of power battery cells disposed within the module housing, a cooling component for heat exchange with the power battery cells, and a cured composite. The cured composite is formed by in-situ curing of the aforementioned composite material within the power battery module and fills at least a portion of the gaps between adjacent power battery cells, between the power battery cells and the module housing, and between the power battery cells and the cooling component. The cured composite forms a continuous contact interface with the plurality of power battery cells and the cooling component. The module housing is provided with a non-filled venting channel that communicates with the safety pressure relief component of the power battery cells.
[0025] Preferably, the thickness of the solidified composite between adjacent power battery cells is 2 mm to 15 mm, and the thickness of the solidified composite between the power battery cell and the cooling component is 0.5 mm to 5 mm.
[0026] Preferably, the cured composite includes a thermally conductive connection area between the power battery cell and the cooling component, and a flame-retardant and heat-insulating area between adjacent power battery cells; the mass percentage of the insulating thermally conductive control unit in the thermally conductive connection area is higher than that in the flame-retardant and heat-insulating area, and the sum of the mass percentages of the reaction-isolated expandable flame-retardant microcapsules and the high-temperature heat-insulating barrier unit in the flame-retardant and heat-insulating area is higher than that in the thermally conductive connection area.
[0027] In some specific embodiments of the present invention, a thermally conductive connection area is formed between the power battery cell and the cooling component, and a flame-retardant and heat-insulating area is formed between adjacent power battery cells. The thermally conductive connection area uses a high content of spherical alumina and hexagonal boron nitride, while the flame-retardant and heat-insulating area uses a high content of reaction-isolated expandable flame-retardant microcapsules, hydrophobic silica aerogel composite microparticles, and silica-coated expandable graphite.
[0028] The two regions can be formed by sequential or dual-path synchronous injection. In the sequential injection method, the thermally conductive bonding zone slurry is first injected into the gap between the power battery cell and the cooling component, and then the flame-retardant and heat-insulating zone slurry is injected into the gap between adjacent power battery cells. The two slurries are brought into contact and cured together before at least one slurry has fully cured. In the dual-path synchronous injection method, the two slurries are injected into the corresponding regions through different inlets, and they come into contact and cross-link at the boundary between the regions to form a continuously cured composite.
[0029] The fifth aspect of the present invention provides the application of the composite material in the preparation of a functional potting compound for lithium-ion power battery modules for new energy vehicles, wherein the functional potting compound is used for at least one of temperature control, thermal runaway propagation suppression, electrical insulation, vibration reduction, impact resistance and structural fixation.
[0030] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention uses a two-component addition-curing organosilicon system as a continuous phase. By controlling the composition and interface state of each functional unit, the uncured composite material can enter the gaps between battery cells and between battery cells and the shell, and cure in situ at the injection site to form a continuous elastic composite, thereby taking into account the injection construction, functional filler fixation and elastic support of module components.
[0031] This invention employs a double-shell phase change microcapsule with a polyurea inner shell and a silica outer shell, confining the phase change core material within the double-layer shell. This helps reduce the risk of leakage of the phase change core material and shell damage during mixing, degassing, filling, and thermal cycling. By using phase change thermal storage units with different phase change temperatures, heat can be absorbed in stages near the normal operating temperature of the battery and at the initial stage of abnormal temperature rise, reducing the risk of rapid local heat accumulation and uneven temperature between battery cells.
[0032] This invention formulates the intumescent flame-retardant component into microcapsules with a reaction-isolating shell, which helps reduce the direct contact between components such as ammonium polyphosphate, pentaerythritol, and melamine and the addition-curing reaction system, thereby mitigating the adverse effects of the flame-retardant component on the platinum catalyst and the curing reaction. The endothermic inorganic flame-retardant unit, the reaction-isolating intumescent flame-retardant microcapsule, and the high-temperature thermal barrier unit work together to respectively perform functions such as heat absorption, dilution of combustibles, expansion into char, and formation of an inorganic thermal barrier under abnormally high-temperature conditions, thereby inhibiting flame propagation and heat spread between adjacent battery cells.
[0033] This invention utilizes silica coating on expandable graphite, combined with hydrophobic silica aerogel and silanized hollow glass microspheres. This approach retains the barrier effect of high-temperature expansion while reducing the adverse impact of direct exposure of conductive carbon materials on the electrical insulation performance of the composite material. The insulating and thermally conductive filler facilitates the establishment of a controlled heat transfer path during normal operation, transferring localized heat to effective heat dissipation areas and avoiding the introduction of continuous conductive pathways.
[0034] This invention can also place composite materials that prioritize thermal conductivity and temperature uniformity and composite materials that prioritize flame retardancy and thermal insulation in different injection areas according to the thermal management requirements of different parts of the battery module. This allows the heat dissipation path under normal operating conditions to cooperate with the thermal insulation path under thermal runaway conditions, thereby improving the adaptability of composite materials to different thermal safety stages and providing a material basis for the integrated thermal management and safety protection of power battery modules. Attached Figure Description
[0035] The present invention will be further described below with reference to the accompanying drawings.
[0036] Figure 1 This is a schematic diagram showing the functional partitioning and distribution of each functional unit when the composite material of the present invention is disposed between adjacent power battery cells; Figure 2 This is a schematic diagram of the process of preparing component A and component B of the composite material of the present invention, including metering and mixing, vacuum degassing, module injection and in-situ curing. Figure 3 This is a schematic diagram showing the relative positions of the power battery cell, the solidified composite, the cooling component, and the directional exhaust channel in the power battery module of the present invention. Figure 4 This is a schematic diagram illustrating the phased response mechanism of the composite material of the present invention during normal operation, abnormal temperature rise, and thermal runaway. Figure 5 This is a schematic diagram of the flame heating and back-side temperature measuring device used in the fire resistance and heat insulation test of this invention; Figure 6 This is a schematic diagram of the thermal runaway triggering and propagation test device for the power battery module of the present invention.
[0037] Figure reference numerals: 1. Power battery cell; 2. Thermally conductive connection area; 3. Phase change heat storage area; 4. High-temperature barrier area; 10. Power battery cell safety pressure relief component; 21. Phase change core material; 22. Polyurea inner shell layer; 23. Silica outer shell layer; 31. Reaction-isolated expandable flame-retardant microcapsule; 32. Aluminum hydroxide particles; 33. Boehmite particles; 41. Hydrophobic silica aerogel composite microparticles; 42. Surface-silanized hollow glass microspheres; 43. Silica-coated expandable graphite; 50. Module shell; 51-55. Power battery cell; 57. Cooling component; 58. 60. Directional exhaust channel; 70. In-situ cured composite; 71. Heat source; 72. Flame rectification component; 73. Sample; 74. Back thermocouple; 85. Data acquisition device; 86. Test cell; 87. Trigger heater; 108. Temperature acquisition point; 109. Group A dispensing procedure; 100. Group B dispensing procedure; 101. Metering and mixing procedure; 102. Vacuum degassing procedure; 103. Module filling procedure; 104. In-situ curing procedure; 205. Normal operation response stage; 206. Abnormal temperature rise response stage; 207. Thermal runaway failure stage. Detailed Implementation
[0038] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0039] raw material: Vinyl silicone oil V-1: viscosity at 25℃ is 1000 mPa·s, vinyl content is 0.5% by mass; vinyl silicone oil V-2: viscosity at 25℃ is 150 mPa·s, vinyl content is 0.8% by mass, used as a reactive diluent; hydrogen-containing silicone oil H-1: viscosity at 25℃ is 50 mPa·s, active hydrogen content is 0.4% by mass; platinum catalyst: vinyl silicone oil dispersion of a caster-type platinum catalyst, with a platinum concentration of 3000 mPa·s. ppm; Curing inhibitors: 1-ethynyl-1-cyclohexanol, purity 99%; n-octadecane: purity 99%; n-eicosane: purity 99%; n-docosahexadecane: purity 99%; isophorone diisocyanate: purity 99%; diethylenetriamine: purity 99%; tetraethyl orthosilicate: mass fraction of silica 28.5%; polyvinyl alcohol: degree of alcoholysis 88%; ammonium polyphosphate: degree of polymerization 1000; pentaerythritol: purity 98%; melamine: purity 99%; expandable graphite: initial expansion temperature 190℃; boehmite: alumina mass fraction 85%; hydrophobic silica aerogel composite microparticles (SA): D 50 The diameter is 50 μm, and the tap density is 0.15 g / cm³. 3 Surface-silanized hollow glass microspheres (HGM): D 50 Its thickness is 40 μm, and its actual density is 0.40 g / cm³. 3 The isostatic compressive strength is 30 MPa; hexagonal boron nitride: boron nitride mass fraction is 99%; fumed silica: specific surface area is 200 m². 2 / g; Silane coupling agent: vinyltrimethoxysilane, purity 98%; Dispersant: polyether modified polysiloxane dispersant, active ingredient mass fraction 10%; Defoamer: organosilicon defoamer; Tracer pigment: iron oxide red.
[0040] Preparation of double-shell microcapsule phase change thermal storage unit: Preparation of the first double-shell phase change microcapsule (MEPCM-1): (1) Mix 65 parts by mass of n-octadecane and 35 parts by mass of n-eicosane, and stir at 50°C for 30 min to obtain 100 parts by mass of molten phase change core material; (2) Add 12 parts by mass of isophorone diisocyanate and 1 part by mass of Span-80 to 100 parts by mass of molten phase change core material, and stir at 50℃ and 300 r / min for 10 min to obtain 113 parts by mass of oil phase. (3) Dissolve 8 parts by mass of polyvinyl alcohol in 392 parts by mass of deionized water to prepare 400 parts by mass of polyvinyl alcohol aqueous solution with a mass fraction of 2%, and adjust the temperature of the aqueous phase to 48°C; (4) Under stirring conditions of 48℃ and 1000 r / min, 113 parts by weight of the oil phase were added to 400 parts by weight of the aqueous phase within 10 min; after the addition was completed, emulsification was carried out at 8000 r / min for 10 min, and then stirring was carried out at 500 r / min for 10 min to obtain D. 50 An emulsion with a thickness of approximately 10 μm; (5) Dissolve 2.20 parts by weight of diethylenetriamine in 20 parts by weight of deionized water and add it dropwise to the emulsion within 30 min under stirring at 400 r / min; after the addition is completed, raise the temperature to 55℃ and react at 400 r / min for 3 h to form a polyurea inner shell on the surface of the emulsion droplets. (6) Add 25 parts by mass of tetraethyl orthosilicate to 60 parts by mass of anhydrous ethanol, add deionized water calculated according to the molar ratio of water to tetraethyl orthosilicate of 4.5:1, adjust the pH to 2.5 with 0.1 mol / L hydrochloric acid, and hydrolyze for 60 min at 25℃ and 300 r / min. (7) Under stirring conditions of 400 r / min, the tetraethyl orthosilicate hydrolysate was added to the polyurea microcapsule suspension within 30 min; the pH of the system was adjusted to 9.5 with 25% ammonia water by mass, and the reaction was carried out at 40℃ and 400 r / min for 3 h to allow silica to be deposited on the outer surface of the polyurea inner shell. (8) After the reaction is complete, filter the solution and wash it twice with 200 parts by weight of anhydrous ethanol, and then wash it with 200 parts by weight of deionized water until the pH of the final water washing filtrate is 7.0±0.2 and the conductivity is ≤100 μS / cm. (9) The washed microcapsules were vacuum dried at 45°C and 10 kPa absolute pressure for 12 h to obtain MEPCM-1; The resulting MEPCM-1 D 50 The measured average value was 9.4±0.6 μm, the phase change peak temperature was 35.1±0.4℃, and the phase change latent heat was 171±4 J / g; the mass fractions of the phase change core material, polyurea inner shell, and silicon dioxide outer shell were 82.0±1.3%, 11.9±0.8%, and 6.1±0.5%, respectively.
[0041] Preparation of the second double-shell phase change microcapsule (MEPCM-2): The difference between MEPCM-2 and MEPCM-1 is that MEPCM-2 uses 30 parts by mass of n-eicosane and 70 parts by mass of n-docosahexanes to prepare 100 parts by mass of phase change core material, while the amount of other raw materials and preparation parameters are the same as those of MEPCM-1. The D of the obtained MEPCM-2 50 The measured average value was 10.1±0.7 μm, the phase transition peak temperature was 43.2±0.5℃, and the latent heat of phase transition was 166±5 J / g; the mass fractions of the phase change core material, polyurea inner shell, and silica outer shell were 81.5±1.5%, 12.1±0.9%, and 6.4±0.6%, respectively. Preparation of Reactive Intumescent Flame Retardant Microcapsules (FRMCs): (1) Ammonium polyphosphate, pentaerythritol and melamine were vacuum dried at 80℃ and 10 kPa absolute pressure for 4 h; 60 parts by mass of ammonium polyphosphate, 20 parts by mass of pentaerythritol and 20 parts by mass of melamine were weighed, 200 parts by mass of anhydrous ethanol were added, and wet ball milling was carried out for 2 h at a ball-to-material mass ratio of 5:1 and a ball milling speed of 300 r / min. (2) Remove anhydrous ethanol under reduced pressure at 60℃, and dry under vacuum at 80℃ and 10 kPa absolute pressure for 4 h to obtain 100 parts by mass of D. 50 An intumescent flame-retardant core material with a thickness of approximately 8 μm; (3) 100 parts by mass of intumescent flame retardant core material were added to an oil phase consisting of 120 parts by mass of cyclohexane, 2 parts by mass of Span-80 and 6 parts by mass of isophorone diisocyanate, and dispersed at 3000 r / min for 10 min to obtain 228 parts by mass of solid-oil dispersion phase. (4) Dissolve 6 parts by mass of polyvinyl alcohol and 0.50 parts by mass of Tween-80 in 394 parts by mass of deionized water to prepare an aqueous phase, and adjust the temperature of the aqueous phase to 30°C; (5) Under the conditions of 30℃ and 1000 r / min, 228 parts by mass of solid-oil dispersion phase were added to the aqueous phase within 15 min, and emulsification was continued for 10 min after the addition was completed; (6) Dissolve 1.1 parts by mass of diethylenetriamine in 30 parts by mass of deionized water and add it dropwise over 30 minutes at 1000 r / min. After the addition is complete, adjust the rotation speed to 500 r / min, raise the temperature to 50℃ and react for 3 hours to form a polyurea primary shell. (7) Remove cyclohexane by depressurization treatment at 40℃ and 20 kPa absolute pressure for 2 h; (8) Add 10 parts by mass of tetraethyl orthosilicate to 50 parts by mass of anhydrous ethanol, add deionized water calculated according to the molar ratio of water to tetraethyl orthosilicate of 4.5:1, adjust the pH to 2.5 with 0.1 mol / L hydrochloric acid, and hydrolyze for 60 min at 25℃ and 300 r / min. (9) Add the hydrolysate to the polyurea-coated particle suspension within 30 min, adjust the pH to 9.5 with 25% ammonia water, and react at 40℃ and 400 r / min for 2 h. (10) After the reaction is complete, filter the solution and wash it twice with 200 parts by weight of anhydrous ethanol, and then wash it with 200 parts by weight of deionized water until the pH of the final water washing filtrate is 7.0±0.2 and the conductivity is ≤100 μS / cm. (11) Vacuum dry at 80℃ and 10 kPa absolute pressure until the moisture content is ≤0.2% to obtain FRMC; The obtained FRMC D 50 The measured average value was 8.1±0.8 μm, the mass fraction of the polyurea primary shell was 4.1±0.5%, the mass fraction of the silica outer shell was 5.7±0.6%, and the total mass fraction of the composite isolation shell was 9.8±0.9%.
[0042] Preparation of silica-coated expandable graphite (SEEG): (1) Weigh 100 parts by mass of D with an initial expansion temperature of 190℃. 50 Expandable graphite with a thickness of 80 μm was vacuum dried at 80 °C and 10 kPa absolute pressure for 4 h. (2) Add 100 parts by weight of expandable graphite to a mixture of 400 parts by weight of anhydrous ethanol and 100 parts by weight of deionized water, add 0.50 parts by weight of hexadecyltrimethylammonium bromide, stir at 500 r / min for 10 min, and then treat with 500W ultrasonic power for 10 min. (3) Add 20 parts by mass of ammonia water with a mass fraction of 25% to adjust the pH of the reaction system to 10.5; (4) Dissolve 30 parts by mass of tetraethyl orthosilicate in 100 parts by mass of anhydrous ethanol, and add it dropwise to the expandable graphite dispersion within 60 min at 25℃ and 500 r / min; continue the reaction for 4 h after the addition is completed. (5) After the reaction is complete, filter the solution and wash it twice with 200 parts by weight of anhydrous ethanol, and then wash it with 200 parts by weight of deionized water until the pH of the final water washing filtrate is 7.0±0.2 and the conductivity is ≤100 μS / cm. (6) The SEEG was obtained by vacuum drying at 80℃ and 10 kPa absolute pressure for 12 h and then sieved through a 120-mesh sieve. The obtained SEEG had a silica coating of 9.1 ± 0.4% and a silica shell thickness of 112 ± 18 nm. 50 The thickness is 85±9 μm, the initial expansion temperature is 190±3℃, the expansion ratio is 245±12 mL / g, and the volume resistivity is 2.6×107Ω·cm.
[0043] The formulations for Examples 1-5 are as follows (by weight percentage):
[0044] Distribution of component A and component B: In Examples 1-5, 50% of the total amount of MEPCM-1, MEPCM-2, aluminum hydroxide, boehmite, spherical alumina, and hexagonal boron nitride were added to components A and B, respectively; 60% of the total amount of FRMC was added to component A, and the remaining 40% was added to component B; SEEG, SA, HGM, silane coupling agent, hydrogen-containing silicone oil H-1, and curing inhibitor were all added to component B; and fumed silica, dispersant, defoamer, platinum catalyst dispersion, and tracer pigment were all added to component A.
[0045] The distribution of vinyl silicone oils V-1 and V-2 in each embodiment is as follows:
[0046] According to the above allocation, component A and component B in each embodiment account for 50% of the total formulation mass, and the mixing mass ratio during use is 1:1.
[0047] Example 1: Balanced composite material and its preparation and infusion Preparation of component A: A vacuum planetary mixer with an effective volume of 5 L and a stirring paddle diameter of 100 mm was used.
[0048] (1) Add the required vinyl silicone oil V-1, vinyl silicone oil V-2 and dispersant to the mixer and stir for 10 min at 25°C and 30 r / min.
[0049] (2) Add all the platinum catalyst dispersion and tracer pigment, and stir for 5 min at 25℃ and 200 r / min.
[0050] (3) Add the required components of component A in sequence: MEPCM-1, MEPCM-2, aluminum hydroxide, boehmite, FRMC, spherical alumina, hexagonal boron nitride, and fumed silica. Stir at 100 r / min for 2 min after each addition, and disperse at 500 r / min for 30 min after all additions. When the impeller diameter is 100 mm, the stirring linear velocity corresponding to 500 r / min is 2.62 m / s.
[0051] (4) Add defoamer, stir at 200 r / min for 5 min, and then defoam at 25℃, absolute pressure of 15 kPa and 100 r / min for 8 min to obtain component A.
[0052] Preparation of component B: (1) Add the vinyl silicone oil V-1, vinyl silicone oil V-2, hydrogen-containing silicone oil H-1 and curing inhibitor required for component B to the mixer and stir for 10 min at 25°C and 30 r / min.
[0053] (2) Add the required components of component B in sequence: MEPCM-1, MEPCM-2, aluminum hydroxide, boehmite, FRMC, spherical alumina, hexagonal boron nitride, and SEEG. Stir at 100 r / min for 2 min after each solid raw material is added, and disperse at 500 r / min for 20 min after all the raw materials are added. The stirring linear velocity is 2.62 m / s.
[0054] (3) Add silane coupling agent and stir at 300 r / min for 5 min.
[0055] (4) Finally, add SA and HGM, and stir at 300 r / min for 20 min. When the diameter of the stirring paddle is 100 mm, the stirring linear velocity corresponding to 300 r / min is 1.57 m / s.
[0056] (5) Degassing was performed at 25℃, 15 kPa absolute pressure and 100 r / min for 8 min to obtain component B.
[0057] Mixing of component A and component B and curing of the sample: Add 500 g each of component A and component B to a mixing container, stir for 2 min at 25℃ and 200 r / min, and then degas for 5 min at 25℃, 15 kPa absolute pressure and 100 r / min to obtain an injectable reactive slurry.
[0058] The slurry was poured into the sample mold and cured at 25°C for 16 h, followed by curing at 50°C for 2 h.
[0059] Power battery module filling: Five square lithium-ion power cells with a rated capacity of 100 Ah are used, with a cell spacing of 8.0 mm and a gap of 1.5 mm between the bottom surface of the cell and the aluminum alloy liquid cooling plate. A continuous venting channel connected to the safety pressure relief component of each cell is set on the top of the module, and the venting channel is temporarily sealed with a removable core mold.
[0060] The module was pre-vacuumed to an absolute pressure of 40 kPa. Slurry was simultaneously injected from the two inlets at the bottom of the module at a single-inlet flow rate of 0.20 kg / min, for a total injection flow rate of 0.40 kg / min. Injection was stopped after the slurry continuously overflowed from the top observation hole for 5 seconds. The module was cured at 25°C for 16 hours, the venting channel core mold was removed, and then post-cured at 45°C for 2 hours.
[0061] The cured body forms an 8.0 mm thick filler layer between adjacent cells and a 1.5 mm thick thermally conductive bonding layer at the bottom of the cell.
[0062] Example 2 High latent heat composite material The difference from Example 1 is that the formulation and component A and B of Example 2 are used; the mass ratio of MEPCM-1 to MEPCM-2 is 2:3; component A and component B are still 50% each, and the mixing mass ratio is 1:1.
[0063] Example 3: High flame-retardant barrier-forming composite material The difference from Example 1 is that the formulation and component A and B of Example 3 are used; the mass ratio of MEPCM-1 to MEPCM-2 is 1:1; the mass ratio of SEEG, SA and HGM is 4:3:3; and component A and component B are still 5% each, with a mixed mass ratio of 1:1.
[0064] Example 4: Low-viscosity, thin-gap composite material The difference from Example 1 is that the formulation and component A and B are as listed in Example 4.
[0065] Example 5: Low-modulus impact-resistant composite material The difference from Example 1 is that the formulation and component A and B of Example 5 are used, wherein the total content of spherical alumina and hexagonal boron nitride is 6.5%, and the content of vinyl silicone oil V-2 is 16%; component A and component B are still 5% each, and the mixing mass ratio is 1:1.
[0066] Comparative Example 1: Basic Organosilicon Encapsulation The difference from Example 1 is that MEPCM-1, MEPCM-2, FRMC, SEEG, SA and HGM are not added, and the spherical alumina content is adjusted to 51.5%.
[0067] Comparative Example 2: Phase Change Encapsulation The difference from Example 1 is that 31% of the double-shell microcapsule phase change thermal storage unit is retained, aluminum hydroxide, boehmite, FRMC, SEEG, SA and HGM are not added, and the content of spherical alumina is adjusted to 34.5%.
[0068] Comparative Example 3: Flame-retardant and heat-insulating potting compound The difference from Example 1 is that MEPCM-1 and MEPCM-2 are not added, and the spherical alumina content is adjusted to 38.5%.
[0069] Comparative Example 4: Simple Blend Composite Materials The difference from Example 1 is that 8% FRMC is replaced with 4.8% uncoated ammonium polyphosphate, 1.6% uncoated pentaerythritol and 1.6% uncoated melamine, and 2% SEEG is replaced with 2% uncoated expandable graphite.
[0070] In preparing component A, 60% of the total amount of uncoated ammonium polyphosphate, uncoated pentaerythritol, and uncoated melamine was added to component A containing the platinum catalyst; the remaining 40% was added to component B. All of the uncoated expandable graphite was added to component B.
[0071] Comparative Example 5: Non-cured phase change slurry material The difference from Example 1 is that a non-reactive dimethyl silicone oil with a viscosity of 500 mPa·s at 25°C is used instead of vinyl silicone oil V-1, vinyl silicone oil V-2 and hydrogen-containing silicone oil H-1, and no platinum catalyst and curing inhibitor are added.
[0072] Non-reactive dimethyl silicone oil, dispersant, and defoamer were stirred at 25°C and 30 r / min for 10 min; the remaining components were added sequentially, and the mixture was dispersed at 500 r / min for 20 min; after adding SA and HGM, the stirring speed was changed to 300 r / min for 20 min; finally, the mixture was defoamed at 25°C, 15 kPa absolute pressure, and 100 r / min for 8 min. The resulting material was a paste-like material that did not undergo cross-linking and curing.
[0073] The formulations for comparative examples 1-5 are as follows (by weight percentage):
[0074] Test method: Unless otherwise specified in relevant standards, three parallel samples are set up for each material performance test, and the average value and standard deviation are reported. Components A and B are conditioned at 25±1℃ for 2 h, then mixed at a 1:1 mass ratio, degassed at an absolute pressure of 15 kPa for 5 min, and then the corresponding samples are prepared.
[0075] 1. Viscosity before curing: The mixed slurry was placed in a thermostatic fixture at 25±0.5℃, using parallel plates with a diameter of 25 mm and a gap of 1.0 mm, and cured for 10 seconds. -1 Pre-shear for 60 s, then proceed for 0.1 s. -1 ~100 s -1 Shear rate scan, recorded for 1 second. -1 10s -1 and 50 s -1 The apparent viscosity at that point.
[0076] 2. Pouring capability: A transparent simulated flow channel with a length of 500 mm, a width of 100 mm, and a gap of 2.0 mm was used. The temperature of the slurry and the flow channel was 25±1℃, and the inlet gauge pressure was 20±1 kPa. The time for the slurry front to reach the end of the flow channel was recorded. After curing, the void volume fraction was determined using industrial CT.
[0077] 3. Curing exothermic reaction: Weigh 500±2 g of the mixed slurry and place it in an insulated container with an inner diameter of 100 mm and an effective depth of 80 mm. The ambient temperature is 25±1℃. Record the peak temperature rise at the center of the sample.
[0078] 4. Curing shrinkage rate: Pour the mixed slurry into a 100 mm × 100 mm × 10 mm mold, cure at 25℃ for 16 h and then at 50℃ for 2 h, and calculate the volume shrinkage rate.
[0079] 5. Elastic modulus: Dumbbell-shaped specimens with a thickness of 2.0±0.2 mm were prepared and conditioned for 24 h at 23±2℃ and 50%±5% relative humidity. The specimens were stretched at a speed of 500 mm / min, and the slope of the curve in the strain range of 0.5%~2.5% was taken as the tensile elastic modulus.
[0080] 6. Volume resistivity: The sample size was 100 mm × 100 mm × 2.0 mm. It was conditioned for 24 h at 23±2℃ and 5%±5% relative humidity. A DC voltage of 500 V was applied and the result was read after 60 s. The sample was then aged for 168 h at 85℃ and 85% relative humidity and then retested.
[0081] 7. Latent heat of phase change: Weigh 8 mg of sample, and use nitrogen gas at a flow rate of 50 mL / min. Perform two heating-cooling cycles at 5℃ / min from 0℃ to 70℃. Calculate the enthalpy of phase change using the second cycle.
[0082] 8. Flame retardant performance: The sample size was 125 mm × 13 mm, and the thicknesses were 1.5 mm and 3.0 mm, respectively. Five samples were tested for each thickness; the limiting oxygen index was also determined.
[0083] 9. Backside temperature rise: The sample size was 100 mm × 100 mm × 8.0 mm, the distance between the heated surface and the flame outlet was 50 ± 2 mm, the heat source temperature was 800 ± 30℃, and the sample was continuously subjected to heat for 10 min. The highest backside temperature and the time to reach 200℃ were recorded.
[0084] 10. Battery Thermal Management: Five square lithium-ion power cells from the same batch, each with a rated capacity of 100 Ah and an initial capacity difference of no more than 2%, were used. The cells were initially charged at 100% and discharged at a 2C rate in an environment of 25±1℃. The cold plate inlet temperature was 25±1℃, and the coolant flow rate was 5.0 L / min. The highest cell temperature and the maximum temperature difference between cells were recorded.
[0085] 11. Thermal runaway propagation: Five square lithium-ion power cells from the same batch, each with a rated capacity of 100 Ah and a state of charge of 100%, were used. A 500 W electric heating plate was installed on the side of the first cell and continuously heated. Heating was stopped after the first cell was triggered to thermal runaway. The number of cells that experienced thermal runaway and the time of the first propagation were recorded within 60 minutes.
[0086] 12. Mechanical protection: The potting module is subjected to a frequency of 10~2000 Hz and an acceleration root mean square value of 27.8 m / s². 2 Random vibrations occurred, lasting 8 hours in each direction; the peak acceleration was 500 m / s². 2 The test involved a 6 ms half-sine mechanical impact, repeated three times in each direction; followed by a 1.0 m drop in the specified direction. After the test, the relative displacement of the battery cells was measured and the cured state was checked.
[0087] Test results: Table 1. Results of rheological, pouring and curing performance tests
[0088] Table 2. Test results of mechanical, electrical, phase change and flame retardant properties of the cured body.
[0089] Table 3 Performance test results of power battery modules
[0090] Preparation of polyurea single-shell phase change microcapsules: The difference between SPCM-1 and MEPCM-1 is as follows: In the oil phase preparation step, the amount of isophorone diisocyanate is adjusted from 12 parts by mass to 18.55 parts by mass; in the interfacial polymerization step, the amount of diethylenetriamine is adjusted from 2.2 parts by mass to 3.4 parts by mass, and the 3.4 parts by mass of diethylenetriamine is dissolved in 20 parts by mass of deionized water; after the polyurea interfacial polymerization reaction is completed, tetraethyl orthosilicate hydrolysis and silica shell coating are not performed, and the product is directly processed according to the washing and vacuum drying conditions of MEPCM-1 to obtain SPCM-1 with only a polyurea shell; the remaining raw materials, raw material amounts, emulsification speed, emulsification time, reaction temperature, reaction time, washing conditions, and drying conditions are the same as those of MEPCM-1.
[0091] The difference between SPCM-2 and SPCM-1 is that SPCM-2 uses 30 parts by mass of n-eicosane and 70 parts by mass of n-docosahexanes to prepare 100 parts by mass of phase change core material; the other raw materials, raw material amounts and preparation parameters are the same as those of SPCM-1.
[0092] Comparative Example 6: Single-shell phase change microcapsule composite material The difference from Example 1 is that 16% of SPCM-1 is replaced by 16% of MEPCM-1 by mass, and 15% of SPCM-2 is replaced by 15% of MEPCM-2 by mass; 50% of the total amount of SPCM-1 and SPCM-2 is added to component A and the remaining 50% is added to component B.
[0093] Comparative Example 7: Composite material without intumescent flame retardant coating The difference from Example 1 is that instead of adding 8% FRMC, 4.80% uncoated ammonium polyphosphate, 1.60% uncoated pentaerythritol, and 1.60% uncoated melamine are added; 60% of the total amount of each of the uncoated ammonium polyphosphate, uncoated pentaerythritol, and uncoated melamine is added to component A containing the platinum catalyst, and the remaining 40% is added to component B; 2% SEEG is still retained, and all of the SEEG is added to component B.
[0094] Comparative Example 8: Uncoated Expandable Graphite Composite Material The difference from Example 1 is that instead of adding 2% SEEG, 2% D, which has an initial expansion temperature of 190°C, is added. 50 The uncoated expandable graphite is 80 μm thick, and all of the uncoated expandable graphite is added to component B; 8% FRMC and its original distribution ratio in components A and B are still retained.
[0095] Comparative Example 9: Single Aerogel Thermal Barrier Composite Material The difference from Example 1 is that 2% SEEG and 1.50% HGM are not added, and the amount of SA is adjusted from 1.50% to 5%, with all of the 5% SA added to component B.
[0096] Comparative Example 10: Thermal Insulation Composite Material of Single Hollow Glass Microspheres The difference from Example 1 is that 2% SEEG and 1.50% SA are not added, and the amount of HGM is adjusted from 1.50% to 5%, with all of the 5% HGM added to component B.
[0097] Comparative Example 11: Single-coated expandable graphite barrier composite material The difference from Example 1 is that 1.50% SA and 1.50% HGM are not added, and the amount of SEEG is adjusted from 2% to 5%, with all of the 5% SEEG added to component B.
[0098] Comparative Example 12: Composite materials in a single low phase transition temperature range The difference from Example 1 is that MEPCM-2 is not added, the amount of MEPCM-1 is adjusted from 16% to 31%, 50% of the total amount of MEPCM-1 is added to component A, and the remaining 50% is added to component B.
[0099] Comparative Example 13: Composite materials with a single high phase transition temperature range The difference from Example 1 is that MEPCM-1 is not added, the amount of MEPCM-2 is adjusted from 15% to 31%, 50% of the total amount of MEPCM-2 is added to component A, and the remaining 50% is added to component B.
[0100] Table 4 Rheological, pouring and curing properties
[0101] Table 5 Mechanical, electrical, phase change and flame retardant properties of the cured body
[0102] Table 6 Performance of Power Battery Modules
[0103] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A pourable, in-situ curable phase change thermal storage, flame-retardant, and heat-insulating composite material, characterized in that, The composite material consists of component A and component B, which are stored separately and undergo a cross-linking and curing reaction after mixing. Based on the total mass of components A and B, the composite material comprises: 20%–38% addition-cured silicone reaction matrix, 25%–40% double-shell microcapsule phase change heat storage unit, 8%–20% endothermic inorganic flame retardant unit, 4%–12% reaction-isolated expansion flame retardant microcapsules, 1%–8% high-temperature thermal insulation barrier unit, 2%–15% thermal insulation and thermal conductivity regulation unit, and 0.2%–3% curing and process auxiliary unit, with the sum of the mass percentages of all components being 100%. The addition-cured organosilicon reaction matrix includes vinyl-terminated polyorganosiloxanes and hydrogen-containing polyorganosiloxanes; The double-shell microcapsule phase change thermal storage unit includes a phase change material core, a polyurea inner shell layer formed by the interfacial polymerization of isophorone diisocyanate and diethylenetriamine, and a silica outer shell layer formed by the sol-gel reaction of tetraethyl orthosilicate and covering the outside of the polyurea inner shell layer. The heat-absorbing inorganic flame-retardant unit includes aluminum hydroxide and boehmite; The reaction-isolated intumescent flame-retardant microcapsule comprises an intumescent flame-retardant core material composed of ammonium polyphosphate, pentaerythritol and melamine, and a polyurea primary shell layer and a silica outer shell layer sequentially covering the outside of the intumescent flame-retardant core material. The high-temperature thermal insulation barrier unit includes hydrophobic silica aerogel composite microparticles, surface silanized hollow glass microspheres, and silica-coated expandable graphite. The insulating and thermally conductive control unit comprises spherical alumina and hexagonal boron nitride; The curing and process support unit includes a platinum-based catalyst and a curing inhibitor.
2. The composite material according to claim 1, characterized in that, Component A comprises vinyl-terminated polyorganosiloxane and platinum-based catalyst, but excludes hydrogen-containing polyorganosiloxane; Component B comprises vinyl-terminated polyorganosiloxane, hydrogen-containing polyorganosiloxane, and curing inhibitor, but excludes platinum-based catalyst; the mixing mass ratio of Component A to Component B is 1:1; the molar ratio of silane-hydrogen bonds in the hydrogen-containing polyorganosiloxane to vinyl groups in the vinyl-terminated polyorganosiloxane is 0.8~1.
5.
3. The composite material according to claim 1 or 2, characterized in that, The phase change material core material includes a first phase change core material and a second phase change core material. The first phase change core material is composed of n-octadecane and n-eicosane in a mass ratio of 65:35, and the second phase change core material is composed of n-eicosane and n-docosahexadecane in a mass ratio of 30:
70. The mass ratio of the first phase change microcapsules using the first phase change core material to the second phase change microcapsules using the second phase change core material is 1:4 to 4:
1. The phase change material core material accounts for 72% to 88% of the mass of the double-shell microcapsule phase change thermal storage unit. 50 The size is 5~15 μm.
4. The composite material according to any one of claims 1 to 3, characterized in that, The mass ratio of ammonium polyphosphate, pentaerythritol, and melamine is 6:2:2; the polyurea primary shell accounts for 2% to 8% of the mass of the reaction-isolated expandable flame-retardant microcapsule, and the total mass of the polyurea primary shell and the silica outer shell accounts for 6% to 14% of the mass of the reaction-isolated expandable flame-retardant microcapsule; the silica coating amount of the silica-coated expandable graphite is 8% to 10% of the mass of the expandable graphite, and the silica shell thickness is 80 to 150 nm.
5. The composite material according to any one of claims 1 to 4, characterized in that, The mass ratio of aluminum hydroxide to boehmite is 1.5:1 to 4:1, and the mass ratio of spherical alumina to hexagonal boron nitride is 3:1 to 5:1; the D of the hydrophobic silica aerogel composite microparticles... 50 The D-value of the surface-silanized hollow glass microspheres is 20~80 μm. 50 The size is 20~60 μm.
6. A method for preparing the composite material according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. The phase change material core material is emulsified and dispersed in an aqueous phase, and isophorone diisocyanate and diethylenetriamine undergo an interfacial polymerization reaction on the surface of the phase change material core material to form a polyurea inner shell layer. Tetraethyl orthosilicate undergoes a sol-gel reaction to form a silica outer shell layer on the outside of the polyurea inner shell layer, thus obtaining a double-shell microcapsule phase change thermal storage unit. S2. Ammonium polyphosphate, pentaerythritol and melamine are mixed in a mass ratio of 6:2:2 to form an intumescent flame-retardant core material, and a polyurea primary shell layer and a silica outer shell layer are formed sequentially on the outside of the intumescent flame-retardant core material to obtain a reaction-isolated intumescent flame-retardant microcapsule. S3. Tetraethyl orthosilicate undergoes an alkaline-catalyzed sol-gel reaction to form a silica shell on the surface of expandable graphite, resulting in silica-coated expandable graphite. S4. Mix vinyl-terminated polyorganosiloxane, platinum catalyst, and at least some of the double-shell microcapsule phase change heat storage unit, endothermic inorganic flame retardant unit, reaction isolation type expansion flame retardant microcapsule, high temperature heat insulation barrier unit and insulation and thermal conductivity regulation unit to obtain component A. S5. Mix the vinyl-terminated polysiloxane, the hydrogen-containing polysiloxane, the curing inhibitor, and the remaining components (excluding component A) to obtain component B. S6. Mix the components A and B by metering and degas under vacuum to obtain an injectable reactive slurry.
7. A potting method for a power battery module for new energy vehicles, characterized in that, include: The A and B components of the composite material according to any one of claims 1 to 5 are metered and mixed and degassed; The mixed injectable reactive slurry is injected from the bottom or lower side of the power battery module, filling at least part of the gaps between adjacent power battery cells, between the power battery cells and the module housing, and between the power battery cells and the cooling components; the injectable reactive slurry is then cured in situ at 10~80°C; wherein, during the injection and curing process, an unsealed venting channel connected to the safety pressure relief component of the power battery cell is maintained.
8. A power battery module for new energy vehicles, characterized in that, The device includes a module housing, a plurality of power battery cells disposed within the module housing, a cooling component that exchanges heat with the power battery cells, and a cured composite formed by in-situ curing of the composite material described in any one of claims 1 to 5; the cured composite fills at least a portion of the gaps between adjacent power battery cells, between the power battery cells and the module housing, and between the power battery cells and the cooling component, and forms a continuous contact interface with the power battery cells and the cooling component; the module housing is provided with an unfilled venting channel that communicates with the safety pressure relief component of the power battery cells.
9. The new energy vehicle power battery module according to claim 8, characterized in that, The cured composite includes a thermally conductive connection area between the power battery cell and the cooling component, and a flame-retardant and heat-insulating area between adjacent power battery cells. The mass percentage of the insulating thermally conductive control unit in the thermally conductive connection area is higher than that in the flame-retardant and heat-insulating area. The sum of the mass percentages of the reaction-isolated expandable flame-retardant microcapsules and the high-temperature heat-insulating barrier units in the flame-retardant and heat-insulating area is higher than the corresponding mass percentages in the thermally conductive connection area. The thickness of the cured composite between adjacent power battery cells is 2-15 mm, and the thickness of the cured composite between the power battery cell and the cooling component is 0.5-5 mm.
10. The application of the composite material according to any one of claims 1 to 5 in the preparation of functional potting compounds for lithium-ion power battery modules for new energy vehicles, characterized in that, The functional potting compound is used for at least one of temperature control, thermal runaway propagation suppression, electrical insulation, vibration reduction, impact resistance, and structural fixation.
Citation Information
Patent Citations
Thermal conduction potting silica gel based on phase-changing microcapsule and preparation method of thermal conduction potting silica gel
CN107815286A
Application of spraying type phase change material in battery and battery
CN113789157A
Ultralow-density super-flame-retardant organosilicon heat-insulation pouring sealant and preparation method thereof
CN115595091A